Dewatering of Loy Yang lignite using microwave irradiation treatment and the microscopic description of the process. Issue 12 (10th September 2019) - Liu, Xiangchun; Yu, Delei; Zhao, Zhigang; Xie, Ruilun; Cui, Ping
Abstract: Loy Yang lignite was dewatered using microwave irradiation (MI) treatment. Residual water content (RWC), energy consumption, total acidity, pore size distribution, and equilibrium water contents (EWCs) at various relative humidities (RHs) were investigated. Furthermore, a microscopic description of the MI dewatering process and water re-adsorption performance of the MI-treated sample were presented. The results showed that RWC and energy efficiency decreased with increasing experimental time and power level. The reason the energy efficiency decreased is because the water remaining in lignite is more and more difficult to be removed. Additionally, ca. 0.08 g of lignite matrix was removed from 1 g of lignite on a dry basis for all the treated samples, indicating that water loss content measured by the mass release observed during MI process is imprecise. Furthermore, the total acidity contents, pore volumes, and EWCs of the treated samples decreased relative to those of raw lignite. The decrease in EWC was enhanced with increasing processing time and power level. The decreased EWC suggests that MI upgraded lignite in terms of reducing water re-adsorption capacity. For the microscopic description of the process, dissolved organic and inorganic compounds are removed from lignite during MI treatment process. EWCs decreased at low and high RHs are ascribed to the decrease in total acidity and the combined effect of the decreases in total acidity and pore volume, respectively.